Effects of droplet size and spray volume parameters on droplet deposition of wheat herbicide application by using UAV - Shan, Changfeng; Wang, Guobin; Wang, Haihong; Xie, Yingjie; Wang, Huizheng; Wang, Shilong; Chen, Shengde; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2021)
With the characteristic of flexible and precise, unmanned aerial vehicles (UAVs) for low volume applications are increasing substantially and quickly around the globe. However, little attention has been paid to the study of wheat herbicides with UAV, especially the research on the spray volume and droplet size of the herbicide sprayed by UAVs. The objectives of this study were to compare the droplet deposition from a typical commercial UAV under four different spray volumes of 7.5 L/hm2, 15.0 L/hm2, 22.5 L/hm2, and 30.0 L/hm2 and three different volume median diameter (VMD) of 150 μm, 200 μm, and 300 μm during winter wheat weeding period. DepositScan software was used to analyze droplet deposition parameters including the percentage of spray coverage and the number of droplets in various sampling positions. The test results showed that the droplet deposition was effected by each factor and their interactions. When the spray volume was 7.5 L/hm2, the effect of VMD on the percentage of spray coverage was not significant. However, these variation rules were changed to smaller droplets with greater coverage when the spray volume higher than 15.0 L/hm2. In all treatments, the number of droplets increased with decreasing VMD or increasing spray volume. The maximum percentage of spray coverage and the number of droplets that were achieved under the VMD of 150 μm and the spray volume of 30.0 L/hm2 were 12.8% and 40.0 droplets/cm2, respectively. The variation coefficients of the percentage of spray coverage and the number of droplets were 29.0%-73.3% and 20.2%-54.1%, respectively. The most uniform deposition was achieved under the spray volume of 15.0 L/hm2 and the VMD of 150 μm. The results revealed the effect of droplet size and spray volume parameters on droplet deposition, which was useful for guiding farmers on how to use UAVs for weeding in winter wheat fields.Keywords: unmanned aerial vehicle, spray volume, droplet size, droplet depositionDOI: 10.25165/j.ijabe.20211401.6129Citation: Shan C F, Wang G B, Wang H H, Xie Y J, Wang H Z, Wang S L, et al. Effects of droplet size and spray volume parameters on droplet deposition of wheat herbicide application by using UAV. Int J Agric & Biol Eng, 2021; 14(1): 74–81.